Implementasi Good Governance Dalam Penyelenggaraan Pemerintahan Daerah di Kota Bukittinggi - Sari, Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The task of the local government as the organizer of government in the region is to provide excellent and maximum public service. The implementation of the principles of good governance is consist in Law Number 28 of 1999 as guidance for local governments to improve public welfare in maximizing public services. Based on the results of research, it can be concluded that the Implementation of Good Governance in the Implementation of Regional Governance in the City of Bukittinggi runs quite effectively at the DPRD as the DPRD as the regional legislative institutions and offices as regional technical implementing units. Constraints that affect the Implementation of Good Governance in the Implementation of Regional Government in Bukittinggi City include the services, constraints experienced include the quality and quantity of human resources, facilities and infrastructure, local regulations that have not yet fully regulated the performance of public services. In DPRD, there are institutional constraints, HR constraints, budget constraints, and regulatory constraints, all of which are related to the DPRD function itself, which results in inaccuracies in performance achievement by DPRD members